Spatio-temporal pattern and entropy variation of agricultural heritage in China - Beichen Ge; Yuhong Song; Jing Wang; Yi Wang; Xi Yuan (Heritage Science)
Abstract As one of the pioneering nations to heed the Food and Agriculture Organization (FOA) initiative, China has implemented a comprehensive evaluation and protection framework for China’s Nationally Important Agricultural Heritage Systems (CNIAHS). This research concentrated on 188 CNIAHS sites, utilizing methodologies including spatial information entropy, kernel density estimation and hotspot analysis to scrutinize the spatial configurations and evolutionary trajectories of CNIAHS throughout six historical epochs; combined with the history of agriculture in different periods, the laws of the formation of CNIAHS spatial distribution are discovered, and a foundation for the construction of CNIAHS protection system under the background of national spatial planning are provided. The results disclose: (1) CNIAHS manifests a clustered spatial distribution, predominantly situated in the southeastern sector of China’s Yangtze River Basin, with Jiangsu, Zhejiang, Fujian, and Jiangxi provinces emerging as significant hotspot areas; (2) concerning spatial pattern evolution, heritage sites experienced a phased transitional process, migrating from western frontier areas to the central Yellow River Basin, subsequently concentrating in the southeastern Yangtze River Basin, and then redistributing back to frontier regions. This progression has cumulatively formed a spatial pattern mainly concentrated in southeastern China; (3) pertaining to typological patterns, high-value crop and spice systems exhibit a clustered spatial distribution, whereas other types display uniform or dispersed configurations; and (4) the complexity of spatial patterns in various regions increased over different periods, with the number of heritage sites demonstrating cumulative characteristics. The spatial patterns indicated weakly correlated transitional shifts, signifying a non-linear progression in the spatial patterns of CNIAHS. (5) The subsequent excavation of CNIAHS should fan out from point to area to promote the exploration of various types of CNIAHS in northeast and southwest China; and the excavation of marine heritage in the southeast China. These insights provide substantial references for the future exploration and preservation of CNIAHS.